The Learning Development Model for Writing Indonesian Child Stories Based on The Character Education to Support The Creative Industry With the Lesson Study - Wahyudi Siswanto; Roekhan Roekhan; Dewi Ariani (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
The purpose of this study was to (1) obtain learning data for writing  Indonesian child stories based on character education, (2) develop a learning model for writing child stories based on character education, and (3) disseminate learning models for writing Indonesian child stories based on character education to support the creative industries in grade 5 of Elementary School with lesson study. These goals are achieved through the development of research methods (Borg & Gall) lesson study. To achieve these objectives, the first phase or the first year I will do theoretical studies and surveys about the learning data writing children's stories Indonesia-based character education. Stage III or the third year will be conducted in the form of dissemination of learning model writing children's stories Indonesia-based character education to support the creative industries in grade 5 of Elementary School with lesson study.